The Relationship between Cash Ratio and Firm Profitability Applied Study on Egyptian Stock Market - Srour, Heba; Srour, Mohamed (International Journal of Membrane Science and Technology, 2023)
Purpose: This paper investigates the relationship between CaHR and firm financial profitability applying to the Egyptian stock market. Methodology: OLS regression analysis is conducted to explain the 2 models used for a sample of (10) Egyptian Companies during the period between 2013 to 2021. The main hypothesis is tested H1: There is no a statistically significant relationship between CaHR and firm profitability. Findings: The independent variables (CaHR, Lev) have a negative effect on ROA-ROE, and the independent variables (size, AG) have a positive effect on ROA-ROE, but all independent variables have a statistically significant relationship on ROA-ROE, and thus the study’s main hypothesis was rejected. Research limitations: The paper opens the area for future research by using a distinct dataset that includes the time period during and after the COVID-19 epidemic to capture the impact of covid-19 on the firm liquidity and profitability.